(untitled) (Ameghiniana, 2013)
"The phytopalaeoecological analysis carried out on ecofacies of the Rio Genoa Formation at Lomas Chatas, has allowed to distinguish four palaeocommunities in a fluvío-deltaic alluvian plain environment. a) Hidro-higrophylous community, composed mainly by Articulates (Equisetales and Sphenophyllales) occupying swampy areas with the water table near the surface of the alluvial plain; b) Higro-mesophylous communities, two kinds have been recognized: one with Glossopteridales, ferns and Progymnosperms and another with Conifers and ferns; both grew on a less restricted environment in the floodplaín with a deeper water table, and e) Mesophylous community: consisting of Glossopteridales and Conifers that inhabited higher areas of the alluvial plain. Probably neat boundaries between palaeocornmunities did not exist and therefore gradational and ecotonal areas developed. Comparisons with palaeocommunities from nearly fossiliferous loealities show the persistence of higro-mesophylous and mesophylous communities while taxonomic changes have been noted in hídro-higrophylous communities."